PERANCANGAN SISTEM INFORMASI JASA LAUNDRY PADA SB LAUNDRY - Prasetyo Adi Nugroho; Sri Susanti (Institut Teknologi dan Bisnis (ITB) Swadharma, 2022)
Currently, the development of information technology has progressed very rapidly. These technological developments cannot be separated from the role of humans who are constantly improving and looking for innovations so that technology can be used to help humans work. Information technology has been widely used in various organizations, both large and small organizations. SB Laundry is one of the businesses in laundry services, located at Jl. KH. Moh. Mansyur, Gg Alkap Market No. 5i. Based on the analysis carried out, the system that runs in business activities still uses a manual system, in this case, the laundry receipt transaction is recorded in the laundry receipt by hand, which allows for data errors in recording laundry service transactions activities. To overcome the weaknesses and threats contained in the laundry service information system, a strategy was chosen by making improvements and developing a computerized system. The new system is expected to improve the quality of laundry service performance and increase the number of customers who come to SB Laundry. By providing training to prospective system users, and providing hardware and software following the analysis of device requirements, so that the system can run as expected.